2022
DOI: 10.2991/978-94-6463-008-4_43
|View full text |Cite
|
Sign up to set email alerts
|

Frugal Lifestyle Trend Among Generation Z

Abstract: This research is based on the phenomenon of Generation Z’s life as the next generation who spends their expenses sparingly due to several current global threats such as the depletion of global resources, the climate crisis, to the Covid-19 pandemic. This frugal lifestyle behavior is characterized differently and for different reasons over time. Therefore, it is necessary to understand frugal living and its relationship with Gen Z as frugal consumers’ acceptance which is also the study’s goal. Data analysis fro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 12 publications
0
1
0
Order By: Relevance
“…The other generations are financially considerate, but not as much as Generation Z. This is also confirmed by evidence of greater frugality among the youngest generation [52]. A previous study of consumers in Kelantan [53] identified the key factors driving Generation Z to purchase snacks: packaging, price, available health information, availability, and taste.…”
Section: Purchase Intentionmentioning
confidence: 88%
“…The other generations are financially considerate, but not as much as Generation Z. This is also confirmed by evidence of greater frugality among the youngest generation [52]. A previous study of consumers in Kelantan [53] identified the key factors driving Generation Z to purchase snacks: packaging, price, available health information, availability, and taste.…”
Section: Purchase Intentionmentioning
confidence: 88%